Management of osteomyelitis in adult wounds: Therapeutic aspects (Research, Society and Development, 2024)
Objectives: to identify in the scientific literature therapeutic methods used for osteomyelitis in chronic wounds in adults and to develop a clinical guide for a federal University Hospital in Rio de Janeiro. Methodology: integrative literature review, whose inclusion criteria were complete articles on therapeutic aspects of osteomyelitis in adult wounds since 2018, in Portuguese, Spanish or English. The systematic electronic search occurred using descriptors in health sciences (DeCS) and Medical Subject Heading (MeSH). Results: 508 articles identified (500 electronic and 08 physical), after reading the abstract by two researchers and excluding duplicates, 76 articles remained selected and included for analysis. The majority of studies were American (42.10%) and published by doctors (92.1%). 98% pointed to microbiological culture and blood tests as guides for therapeutic parameters, in addition to imaging tests as complementary (20%). Surgical debridement was the most used procedure (82.3%) to remove bone infection. There was no therapeutic consensus, but recommendations for good practices, which are included in the clinical guide for treating wounds with osteomyelitis prepared based on this review. Conclusion: the lack of consensus and the scarcity of literature, especially nationally, may be compromising safety and quality of care. Therefore, nurses, especially specialists in dermatological nursing/stomatherapy, must exercise leadership in early clinical assessment with a view to referrals for medical diagnostic confirmation . And with this, accelerate the initiation of the most appropriate treatment guided by tests, which could prevent complications and the chronicity of a public health problem.